The Influence of Intrapersonal Intelligence on Mathematics Learning Achievement - Asido Saragih (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Difficulty learning mathematics is a problem that often occurs, and this condition is considered to give a stigma that mathematics is a difficult subject. Various learning theories and approaches have been used, including recognizing, and exploring students' potential to find out whether there is other potential that can support their ability to understand mathematics, such as the ability to understand and evaluate oneself, also known as intrapersonal intelligence. This research aims to measure the influence of students' intrapersonal intelligence on their mathematics learning achievement by distributing questionnaires to measure their intrapersonal intelligence, as well as students' report cards as a representation of their mathematics learning achievement. In this study, the researcher used quantitative methods and found a positive and significant influence between intrapersonal intelligence on mathematics learning achievement on a strong scale.